Low Loss Hollow-Core Connecting-Circle Negative-Curvature Fibres - Boyi Yang; Xuesheng Liu; Wenzeng Jia; Shu Liu; Kai Mei; Tingwu Ge; Dengcai Yang; Youqiang Liu; Tian Lan; Zhiyong Wang (IEEE Photonics Journal, 2021)
Hollow-core negative-curvature fibres have been the focus of current research, but how to reduce the loss of hollow-core negative-curvature fibres is a serious problem. This paper proposes a new structure of hollow-core negative-curvature fibres, that is numerically simulated using the finite-element method, and compared with the simulation results of hollow-core conjoined-tube negative curvature fibres (CTNCFs) and hollow-core nested anti-resonant nodeless fibres (NANFs). The results show that, the LP01 mode loss can reach 0.003694 dB/km with a transmission wavelength of 1.06 μm, the LP11 mode loss can be as low as 0.28423 dB/km, and the bending loss is 0.4405 dB/km with a bending radius of 5 cm and a transmission wavelength of 1.06 μm. The loss is reduced by an order of magnitude compared to CTNCFs and NANFs.